Determinants of customer's intention to use Islamic personal financing - Nurul Harisah, Ahmad (2014)
This study investigates the determinants of customer‟s intention to use Islamic personal financing by measuring the following factors: attitude; social influence; religious obligation and pricing, on the intention to use Islamic personal financing. This research also examines the relationships between the customer‟s intention and its determinants. The sample comprised of 250 customers of full-fledged Islamic bank in Kedah which is Bank Islam Malaysia Berhad (BIMB) Alor Setar. Data were obtained through a face-to-face survey using structured questionnaire . Out of a total of 250 responses, only 200 responses were usable for further analysis. The study used correlation and regression to analyze the collected data. The study found three determinants to be significant in influencing the intention to use Islamic personal financing, namely, attitude, social influence and religious obligation. Apart from that, pricing of Islamic personal financing was found to be insignificant predictors. The findings of this study provide invaluable insights into factors affecting the bank customers‟ intention to use Islamic personal financing, especially in the case of Malaysian Islamic banks. This empirical study on the determinants of Islamic financing using the survey method contributes towards a better understanding of the customers‟ expectations for Islamic financial products. Managers of Islamic banks can now comprehend better the factors that influence bank customers‟ decision in patronizing Islamic personal financing. On the other hand, the findings of this study should be of value to Islamic banks in terms of expanding their customer base.